ANALYSIS OF THE EFFECT OF COMMITMENT, LOYALTY, AND TEAMWORK ON EMPLOYEE PERFORMANCE IN PT. SUJATI SINAR SEMPURNA - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to analyze the effect of commitment, loyalty, and teamwork on employee performance at PT. Sujati Sinar Sempurna either partially or simultaneously. This study uses multiple linear regression analysis using the SPSS version 20 application, with a total sample of 40 employees at PT. Sujati sinar sempurna Pekanbaru. The results of the overall research variable loyalty, and teamwork affect the performance of employees at PT. Sujati Sinar Sempurna, while commitment has no effect on employee performance at PT. Sujati sinar sempurna Pekanbaru. Commitment, loyalty, and teamwork variables have contributed 97.1% to the performance variable, although there is still 2.9% influence on other factors not included in the study.